FEATURES OF TREATMENT FOR ARTICULAR SYNDROME IN ELDERLY PATIENTS WITH ARTERIAL HYPERTENSION SPECIFIC - I V Egorov; V V Tsurko; I V Egorov; V V Tsurko (Современная ревматология)
A patient with the articular syndrome and arterial hypertension (AH) is well known to have elevated blood pressure levels with co-administration of nonsteroidal anti-inflammatory drugs and most classes of antihypertensive agents. This effect may be attended by a higher risk for cardiovascular events. A physician's task is to choose the most optimal treatment regimen for musculoskeletal disease in patients with AH. Nimesulide may be the drug of choice in treating this group of patients.